2017
DOI: 10.1080/20016689.2017.1393308
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of ibrutinib in patients with Waldenström macroglobulinemia in Italy

Abstract: Background and Objective: Ibrutinib has recently been approved in Europe for Waldenström Macroglobulinemia (WM) in symptomatic patients who have received at least one prior therapy, or in first-line treatment for patients unsuitable for chemo-immunotherapy. The aim of the study is to estimate the incremental cost-effectiveness ratio (ICER) of ibrutinib in relapse/refractory WM, compared with the Italian current therapeutic pathways (CTP). Methods: A Markov model was adapted for Italy considering the National H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, as the cost of Ibr treatment is very high, Olszewski et al [14] examined the cost-effectiveness of Ibr use compared with chemo-immunotherapy. Italian medical and economical experts analyzed the cost-effectiveness of single-agent Ibr compared with the Italian current therapeutic pathways (CTP) for relapse/refractory WM by using an incremental cost-effectiveness ratio [15]. They concluded that Ibr increased the Life Years Gained and costs were comparable with CTP.…”
mentioning
confidence: 99%
“…However, as the cost of Ibr treatment is very high, Olszewski et al [14] examined the cost-effectiveness of Ibr use compared with chemo-immunotherapy. Italian medical and economical experts analyzed the cost-effectiveness of single-agent Ibr compared with the Italian current therapeutic pathways (CTP) for relapse/refractory WM by using an incremental cost-effectiveness ratio [15]. They concluded that Ibr increased the Life Years Gained and costs were comparable with CTP.…”
mentioning
confidence: 99%